Digital Competency for Employees in the Banking Industry: Literature Review - Martini, Endang; Damayanti, Rosita Mei; Palupi, Rosa De Lima Dyah Retno; Pramesti, Diah; Ayuninggar, Lintang; Rosdaliva, Mehilda (Jurnal Akuntansi dan Bisnis, 2025)
This study examines how digital skills are developed among banking employees, especially in countries that are still growing their digital systems. Although many models like the Technology Acceptance Model (TAM), Unified Theory of Acceptance and Use of Technology (UTAUT), and Diffusion of Innovation (DOI) have been used to study how people adopt technology, the results often differ between developed and developing countries. By reviewing past research, this study identifies the key factors that influence digital skills, such as how useful or easy a technology is to use, support from others, and how well the technology fits user needs. It also shows that in developing countries, trust, digital knowledge, and access to technology are especially important. The study ends by highlighting the need to connect digital transformation with employee skill development, especially in the banking and finance sector.